Cell size is a key ecological trait associated with biogeographic patterns of microbial eukaryotes in coastal waters - Wu, Wenxue; Liu, Hongbin (Frontiers in Marine Science, 2022)
Body size is an important ecological trait, but it has been poorly explored in microbial communities. Here, we examined the effect of cell size on coastal eukaryotic communities across a size continuum of 0.2–3 (pico-), 3–20 (nano-), and 20–200 μm (micro-sized), which were characterized via high-throughput sequencing based on the V4 region of the 18S rRNA gene. We found that, at the alpha diversity level, there was a decreasing trend across the pico-, nano-, and micro-sized eukaryotic communities regarding both amplicon sequence variant (ASV) richness and Shannon index. At the beta diversity level, the three categories were significantly different, and these were accompanied by a relatively high local contribution to beta diversity in contrasting freshwater and seawater locations. The community variations observed for the microbial eukaryotes could largely be explained by the environmental effects which decreased between the pico- (40.5%), nano- (37.3%), and micro-sized (27.3%) fractions. These environmental effects were mainly contributed by several ASV modules showing opposing responses to environmental conditions. This might partly indicate the coalescence of the freshwater and seawater groups of microbial eukaryotes. In summary, our findings suggest that the cell size of microbial eukaryotes is a phylogenetically conserved trait, which is tightly associated with biogeographic patterns.